Penyembunyian Pesan Rahasia Pada Citra Digital dengan Teknik Steganografi Menggunakan Metode Least Significant Bit (LSB ) - Lasarus Pelipus Malese (Jurnal Ilmiah Wahana Pendidikan, 2021)
The rapid development of digital media and its use in various fields raises greater demands to create an information delivery system that is guaranteed to be secure. One of them is with steganography. Steganography is a method for inserting pieces of confidential information in an object or other media. With steganography, information is hidden in such a way that its whereabouts are unknown, which is known as information hiding. This method is different from the cryptographic method, which encodes existing information so that it cannot be read without knowing the key or password used, but its existence is still known and not hidden. This final project was developed using Microsoft Visual Basic 6.0 implementing the Simple Least Significant Bit Substitution ("simple LSB substitution") steganography method to hide information into a multimedia file. Multimedia files used are image files, audio files, and video files as a medium for carrying confidential information. The use of steganography technology is expected to increase security in the delivery of information, so that important information will be protected and its presence disguised in multimedia files. This is also expected to help the process of protecting the copyright of electronic media works.